Prospective cohort study of incidence and risk factors for catheter-associated urinary tract infections in 145 intensive care units of 9 Latin American countries: INICC findings - Yin, Ruijie (2023)
Purpose: Identify urinary catheter (UC)-associated urinary tract infections (CAUTI) incidence and risk factors (RF) in Latin American Countries. Methods: From 01/01/2014 to 02/10/2022, we conducted a prospective cohort study in 145 ICUs of 67 hospitals in 35 cities in nine Latin American countries: Argentina, Brazil, Colombia, Costa Rica, Dominican Republic, Ecuador, Mexico, Panama, and Peru. To estimate CAUTI incidence, we used the number of UC-days as the denominator, and the number of CAUTIs as numerator. To estimate CAUTI RFs, we analyzed the following 10 variables using multiple logistic regression: gender, age, length of stay (LOS) before CAUTI acquisition, UC-days before CAUTI acquisition, UC-device utilization (DU) ratio, UC-type, hospitalizationtype, ICU type, facility ownership, and time period. Results: 31,631 patients, hospitalized for 214,669 patient-days, acquired 305 CAUTIs. The pooled CAUTI rate per 1000 UC-days was 2.58, for those using suprapubic catheters, it was 2.99, and for those with indwelling catheters, it was 2.21. The following variables were independently associated with CAUTI: age, rising risk 1% yearly (aOR = 1.01; 95% CI 1.01–1.02; p < 0.0001 female gender (aOR = 1.28; 95% CI 1.01–1.61; p = 0.04), LOS before CAUTI acquisition, rising risk 7% daily (aOR = 1.07; 95% CI 1.06–1.08; p < 0.0001, UC/DU ratio (aOR = 1.14; 95% CI 1.08–1.21; p < 0.0001, public facilities (aOR = 2.89; 95% CI 1.75–4.49; p < 0.0001. The periods 2014–2016 and 2017–2019 had significantly higher risks than the period 2020–2022. Suprapubic catheters showed similar risks as indwelling catheters. Conclusion: The following CAUTI RFs are unlikely to change: age, gender, hospitalization type, and facility ownership. Based on these findings, it is suggested to focus on reducing LOS, UC/DU ratio, and implementing evidence-based CAUTI prevention recommendations.